INTERNALISASI NILAI KEARIFAN LOKAL PELA GANDONG DALAM MANAJEMEN SUMBER DAYA MANUSIA UNTUK PENINGKATAN KINERJA GURU - Liyona Aty R Puttileihalat; Rudolf Kempa; Paul Arjanto (STKIP Subang, 2026)
This study examines the internalization of Pela Gandong local wisdom values within human resource management (HRM) as a strategy for improving teacher performance at SD Inpres 21 Ambon, Nusaniwe District, Ambon City, in the Academic Year 2025/2026. Employing a qualitative approach with a single instrumental case study design (Stake, 1995), this research explores how Pela Gandong values — Masohi (mutual cooperation), Ain ni ain (mutual assistance), Hidup orang basudara (brotherhood across religious and ethnic lines), and Sasi (respect for communal rules) — are operationalized by the school principal in HRM practices, and their impact on organizational climate and teacher performance. Data were collected through in-depth interviews with 9 key informants (principal, 4 senior teachers, 2 junior teachers, 1 school committee member, and 1 supervisor), participatory observation over 4 weeks (July–August 2025), and document analysis. Data analysis employed the Miles, Huberman, and Saldaña (2014) interactive model using NVivo 14. Findings reveal that SD Inpres 21 Ambon has developed four distinctive Pela Gandong-based managerial mechanisms: inter-religious Masohi teacher groups, consensus-based (musyawarah mufakat) staff meetings, Ain ni ain mentoring for junior teachers, and a Sasi-based community agreement. These mechanisms strengthen bridging social capital, foster collective professional identity, and enhance affective commitment to the school — collectively driving sustained improvement in teacher performance. This study contributes the MSDM-KL Model (Local Wisdom-Based HRM) as an original three-layer conceptual framework: values — practices — outcomes, with significant policy implications for educational HRM in Maluku Province.